Model of Structural Organization of Professional Teacher’s Tolerance - Gayduk, Galina (Psychological Prospects Journal, 2018)
This article is devoted to the attempt to construct a theoretical model of structural organization of professional teacher’s tolerance. The analysis of theoretical and empirical research on the personality problem of the teacher enabled to focus on the specific approach of the close relationship between the teacher’s professional tolerance and his personality, and to establish the need to distinguish between psychological factors, which in their totality and consistency are the key to successful professional implementation in the pedagogical activity. The theoretical model of the structural organization of the teacher’s professional tolerance was developed on the basis of the definition it to be a system of personality characteristics that determine a stable awareness of the leading professional roles, values, and norms of the teacher and initiate the development of a professional culture of humane and tolerant attitude to other people. This model includes such components as cognitive-informative, emotional-regulatory, person-communicative and behavioral-normative. The above-mentioned components of teacher’s professional tolerance are closely interrelated and constitute a complex of cognitive, emotional, personal and behavioral characteristics of a specialist, which encompasses the assessment of opportunities and the acquisition of the respective features of a tolerant personality. Each of them contains the motivational signs of professional self-realization of the teacher, which are motivated in the motivational-semantic modes of their productive functioning: operational-semantic modes, reflexive-semantic modes, motivational-regulating (internal) modus, and motivation-controlling (external) modus.